Representasi Komunikasi Politik Tanpa Moralitas Perspektif Filsuf Modern Niccolo Machiavelli - Felisianus Efrem Jelahut; Monika Wutun; Henny L. L. Lada; Abner Paulus Raya Sanga (Jurnal Filsafat Indonesia, 2023)
The purpose of this study was to determine the representation of political communication without morality from the perspective of the modern philosopher Niccolo Machiavelli. The focus of this research is the concept of political thought without morality by Niccolo Machiavelli. Machiavelli's concept of thought is a completely new methodology in political studies. This change does not lie in its orientation to the analysis of real political behavior because in the previous centuries Aristotle had collected factual data as a requirement for political formulation. Instead he seeks to completely separate the ethical context from political reality. This study uses a qualitative method with the type of literature study in which the researcher traces the important relevant works of the political philosopher Niccolo Machiavelli. The results of the study describe the representation of political communication in the concept of politics without morals along with the functions of the concept.